Success Factors of Regional Strategies for Multinational Corporations Appropriate Degrees of Management Autonomy and Product Adaptation - Heinecke, Patrick; SpringerLink (Online service). (Heidelberg Physica-Verlag HD, 2011)
This work examines the factors that drive the success of Multinational Corporations (MNCs) in their pursuit of regional strategies. The author develops a comprehensive regional success factor model, by which the effects of regional management autonomy and regional product and service adaptation on the regional success of MNCs as well as the interaction effects of regional orientation and inter-regional distance are investigated. The model is evaluated by means of the partial-least-squares (PLS) method on the basis of a survey-based inquiry of the Fortune Global 500 firms with success indicator data for a period of nine years. The findings highlight the importance of considering the different degrees of contextual influence in the design of regional strategies, where low degrees of regional management autonomy and high levels of regional product/service adaptation are found to be appropriate for MNCs to be regionally successful.
Part I: Theoretical Setting for Regional Strategies and Regional Success -- 1 Introduction -- 2 Theoretical Foundation and Literature Review -- Part II: Development of a Regional Success Factor Model for the Analysis of the Regional Strategy-Success Relationship -- 3 Structural Equation Methodology -- 4 Regional Success Factor Model -- Part III: Success Factors of Regional Strategies: A New Perspective on the Geographic Competitiveness of Multinational Corporations -- 5 Research Design and Research Methodology -- 6 Empirical Results -- 7 Discussion of Results and Implications -- 8 Conclusions -- 9 Appendix.
Electronic reproduction.
Keywords: International business enterprises -- Management; International business enterprises -- Management -- Cross-cultural studies; Electronic books